The core curriculum in cariology: fiction or reality? Challenges about implementation - Santamaría, Ruth M; Fontana, Margherita; Chalas, Renata; Guzman-Armstrong, Sandra; Kolker, Justine L; Krithikadatta, Jogikalmat; Kuzmina, Irina; Maltz, Marisa; Martignon, Stefania; Ottolenghi, Livia; Pitts, Nigel; Abdin, Maria; et al. (Caries Research, 2024)
Introduction: The Core Curriculum in Cariology (CCC) was developed by ORCA and ADEE in 2010. This article summarizes challenges for the implementation of the CCC at university/country level identified at the "Education Platform" of the ORCA 2022 conference in Cagliari, Sardinia. Methods: Participants from Universities from 3 European (Italy, Poland, and UK), 2 Asian (India and Russia), and 3 American countries (Brazil, Colombia and USA) led the presentations, discussion, and generation of statements. Presentations were transcribed and summarized through qualitative content analysis. Key themes were identified, transformed into key topics, and sent to the panel for agreement. Results: Regardless of the wide variety of dental schools per country, from few (Poland n=10) to many (India n=318, Brazil n=563), or from country/continent itself, frequent challenges to CCC implementation were highlighted. These included: lack of agreement on a basic CCC as standard (96%), insufficient support or reimbursement for caries prevention and management (90%), separation between cariology and restorative dentistry (68%), focus on restorative/surgical management with prevention and non-operative management being disconnected (73%). The group agreed that the integration of cariology and restorative dentistry remains essential to enhancing evidence-based decision-making, resulting in a shift of emphasis from cure to care. Conclusion: There is variation in the level of implementation of the CCC. A frequent challenge is the disconnect between cariology and restorative dentistry. The CCC should be disseminated and promoted as a uniform blueprint/framework to facilitate the implementation of a common cariology curriculum among universities within each country, as well as internationally.